Association of self-leadership and epidemic risk perception on quality of life in post-pandemic mainland of China: a cross-sectional study - Ren, Jiaju; Zhu, Yanbo; He, Yuan; Zhao, Xinyuan; Pang, Guoming; Long, Liqun; Zhang, Qian (Frontiers in Public Health, 2024)
Background Self-leadership has proven to adjust individual psychological states and promote active behaviors to mitigate stress perception and negative lifestyle. This study aims to investigate the relationship between self-leadership, epidemic risk perception, and quality of life among the general public in post-pandemic mainland of China. Methods Two online self-reported questionnaire surveys were carried out with 3,098 and 469 people in the Chinese mainland in February 2021 and December 2022, respectively. The univariate analysis, structural equation modeling, and fuzzy-set qualitative comparative analysis were used to analyze the data which was collected by Revised Self-Leadership Questionnaire, Perceived Risk of COVID-19 Pandemic Scale and World Health Organization Quality of Life Brief Scale. Results The Self-leadership was directly, moderately, and positively correlated with quality of life (Standardized path coefficients: 0.383 and 0.491, respectively; p < 0.05), and epidemic risk perception was negatively correlated with quality of life (Standardized path: 0.068 and 0.120, respectively; p < 0.05). The structural equation model for self-leadership, epidemic risk perception, and quality of life had a good fit (CFI = 0.957, 0.939 > 0.9; RSMEA = 0.058, 0.064 < 0.08, respectively) and was consistent across genders, educational levels, and types of occupations (Delata-CFI < 0.01). The core condition for achieving a high quality of life lies in maintaining a low level of self-punishment and a high level of self-cueing or a high level of self-punishment and a low level of self-cueing. Conclusion In the post-epidemic era, the public can adjust their attitude toward stress by enhancing their self-leadership skills. Among various self-leadership skills, self-punishment or self-cueing may have the most significant impact on the quality of life.